CRITICAL ANALYSIS OF THE CONCEPT OF INTERNAL RATE OF RETURN OF INVESTMENTS PROJECTS - A. Kuznetsov (Вестник университета)
The article deals with to the critical analysis of the internal rate of return, which represents one of the traditional most frequently used indicators of financial effectiveness of investment projects, allowing investors to sense relative yield from investing in a project. Within the analysis the author identifies deficiencies of applying the internal rate of return and offers alternative means of practical evaluation of relative yield from investing in a project based on modelling of an investor’s behavior related to expected schedule of return invested capital.